Odpowiedzi

2013-07-22T09:20:37+02:00

Zad.4

(x - 2)² = (x - 1)(x + 1)

x² - 4x + 4 = x² - 1

-4x = -1 - 4

-4x = -5   /:(-5)

x = 5/4

----------

 

(x + 1)/2 - 1 = 2x - 2⅜

(x + 1)/2 - 1 = 2x - ¹⁹/₈   I*8

4(x + 1) - 8 = 16x - 19

4x + 4 - 8 = 16x - 19

4x - 16x = -19 + 4

-12x = -15   /:(-12)

x = 15/12

x = 5/4

-----------

Osp. Wskazane  równania mają te same rozwiązania.

 

Zad.5

(a⁵ * a³)² : a*a⁻³ = (a⁸)² : a⁻² = a¹⁶ : a⁻² = a¹⁶⁺² = a⁸

a ≠ 0

 

Zad.7

2(x + 3) = y

3y - ½ x = (y-x)/2  I*2

 

2x + 6 = y

6y - x = y - x

 

2x - y = -6

     5y = 0

 

y = 0

-------

2x = -6  /:2

x = -3

--------

 

{x = -3}

[y = 0}